Gut Dysbiosis and Kidney Diseases - Cao, Chujin; Zhu, Han; Yao, Ying; Zeng, Rui (Frontiers in Medicine, 2022)
Gut dysbiosis is defined as disorders of gut microbiota and loss of barrier integrity, which are ubiquitous on pathological conditions and associated with the development of various diseases. Kidney diseases are accompanied with gut dysbiosis and metabolic disorders, which in turn contribute to the pathogenesis and progression of kidney diseases. Microbial alterations trigger production of harmful metabolites such as uremic toxins and a decrease in the number of beneficial ones such as SCFAs, which is the major mechanism of gut dysbiosis on kidney diseases according to current studies. In addition, the activation of immune responses and mitochondrial dysfunction by gut dysbiosis, also lead to the development of kidney diseases. Based on the molecular mechanisms, modification of gut dysbiosis via probiotics, prebiotics and synbiotics is a potential approach to slow kidney disease progression. Fecal microbiota transplantation (FMT) is also a promising choice. However, the clinical use of probiotics in kidney disease is not supported by the current clinical evidence. Further studies are necessary to explore whether the causal relationships of gut dysbiosis and kidney diseases or the efficiency and safety of therapeutic strategies targeting gut dysbiosis.